The relationship between Product Innovative Strategies and Performance of Kenya Tea Development Agency Factories in Kenya - Chepngetich Dorothy, Koech; Lydia, Langat; Alfred, Bett (International Journal of Scientific Research and Management (IJSRM), 2022)
Kenya Tea Development Agency’s primary role is to collect plucked tea, process and market tea products on behalf of farmers. Despite the crucial role it plays in Kenya’s economy, the tea sector still faces various challenges such as high cost of production, fluctuations in the international market, and emerging issues such as COVID-19 pandemic. To effectively improve the performance of the tea industry, product innovative strategy practices are widely acknowledged for improving productivity and competitiveness in the sector. This study aimed at establishing the relationship between product innovative strategies and performance of KTDA factories in Kenya. It was premised on Schumpeterian theory of innovation and Discovery theory. A correlational and cross-sectional research design was adopted in this study. The target population was 974 employees from 71 KTDA factories in Kenya.  A sample of 283 respondents was drawn from four regions using a stratified sampling method. The main instrument of data collection was a semi-structured questionnaire administered to top, middle, and lower-level employees of KTDA factories in Kenya. The questionnaire was pre-tested to ensure its validity and reliability. An aggregate Cronbach Alpha coefficient of 0.703 was obtained. Multiple linear regression and model was employed to determine the significance of the hypothesis. The findings revealed that product innovative strategies (β = 0.695, R=0.748, p